2017
DOI: 10.1016/j.jtho.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of High-Risk Lung Cancer Screening and Drivers of Program Efficiency

Abstract: Non-lung cancer outcomes drive screening efficiency in diverse, tobacco-exposed populations. Use of risk selection can reduce the budget impact, and screening may even offer cost savings if noncurative treatment costs continue to rise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 38 publications
0
96
1
2
Order By: Relevance
“…For instance, the ICER value of a study based on SEER National Cancer Database in the United States was presented as 116,300 USD/QALY [15] The Markov model was also applied in that study to simulate the annual LDCT screening on lung cancer received by those severe smokers at age of 60. The ICER value (116,300 USD/QALY) of screening strategies in that study far greater than ours (13,736 USD/QALY). The gap originates from the discrepancy in the costs of screening and biopsy diagnosis(300 USD for LDCT screening in that study and 68 USD in this one, the cost for biopsy diagnosis also outweigh ours a lot).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…For instance, the ICER value of a study based on SEER National Cancer Database in the United States was presented as 116,300 USD/QALY [15] The Markov model was also applied in that study to simulate the annual LDCT screening on lung cancer received by those severe smokers at age of 60. The ICER value (116,300 USD/QALY) of screening strategies in that study far greater than ours (13,736 USD/QALY). The gap originates from the discrepancy in the costs of screening and biopsy diagnosis(300 USD for LDCT screening in that study and 68 USD in this one, the cost for biopsy diagnosis also outweigh ours a lot).…”
Section: Discussioncontrasting
confidence: 55%
“…However, these conclusions were not consistent due to the differences in the cost of diagnosis and treatment and the incidence of lung cancer in various countries. Some studies showed that screening is cost-effective [11][12][13] and the others are different [14,15] . At present, there are few studies on the costeffectiveness of lung cancer screening in China [16] .…”
Section: Introductionmentioning
confidence: 99%
“…32,33,41 However, data demonstrating that the balance of harm, benefits, and costs can be optimized with the use of lung cancer risk prediction tools are mounting. 42,43 These tools are now being incorporated into trial eligibility criteria [44][45][46] and are expected to improve screening effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Policy decisions to implement LCS programmes are limited by the availability of population-level evidence to predict health system and public health impacts. Simulation models have been used to overcome this limitation [145]. An analysis of the NLST data estimated that the cost of LCS would be USD 81 000 per QALY gained [23], which is well below the threshold considered reasonable in the USA of USD 100 000 per QALY gained.…”
Section: Cost-effectiveness Of Lcsmentioning
confidence: 99%